TRANSNATIONAL POLLUTION AND COASIAN BARGAINING APPROACH - A COMPARISION BETWEEN THE CASE OF TRANSBOUNDARY HAZE POLLUTION IN SOUTH EAST ASIA AND TRANSFRONTIER WATER POLLUTION IN NORTH AMERICA - Thi Minh Ngoc, Vu (Journal of Forestry Science and Technology, 2016)
Pollution has been accepted as an unavoidable price of material advancement and an inevitable result of an expanding industrial base. In addition, pollution now has become not only a within country problem but also an international environmental issue. Compare to national environmental problems, transnational environmental pollution problems, have some similar characteristics but are far more complicated and need to be dealt with by applying special methods. One of the effective solutions is Coasian bargaining process. This paper compares and analyses the two case of transborder pollution problems, which are transboundary haze pollution in South East Asia and transfrontier water pollution (TWP) in North America. The result shows that the Coasian method is more efficient when applied in the case of TWP. The reasons are that TWP case has less parties involved, more appropriate cost sharing principle and lower transaction cost. Base on this comparison, the paper makes a recommendation that an institute should be established under the THP case to improve the enforcement and monitoring system and a revision on cost sharing system under THP case should also be conducted.